A comparison of the shaping ability of three nickel-titanium rotary instruments: a micro-computed tomography study via a contrast radiopaque technique in vitro. Issue 1 (December 2017) - Wei, Zhao; Cui, Zhi; Yan, Ping; Jiang, Han
Abstract Background Micro-CT (μCT) studies that combine simulated canals with meglucamine diatrizoate to evaluate the shaping ability of nickel-titanium (NiTi) rotary instruments are lacking in the literature. The purpose of this study was to evaluate the shaping ability of three new different nickel-titanium rotary instruments in simulated root canals using μCT. Methods Thirty simulated root canals with a curvature of 60° were randomly allocated into the following 3 groups (n  = 10): Group 1, ProTaper Universal (PTU) rotary system; Group 2, Reciproc single-file system; and Group 3, K3XF rotary system. Pre- and post-instrumented images of simulated canals were scanned with μCT via a radiopaque contrast technique to build a 3-dimensional (3D) model. Canal transportation, volumetric change and centring ability were evaluated in each group. Instrument failure and preparation time were also recorded. The Kruskal-Wallis test was used for statistical analysis and the significance level was set atp  = 0.05. Results Reciproc produced greater volume change in the apical part of the canals compared with PTU and K3XF (p  < 0.05). K3XF exhibited less transportation and better centring ability at the 2- and 3-mm levels from the apical foramen compared with PTU and Reciproc (p  < 0.05). There were no significant differences in the centring ratio and transportation between PTU and Reciproc. Preparation time was significantly shorter in the Reciproc group (p  < 0.05). Conclusions Under the conditions of our study, all of the canals were 3D reconstructed successfully via the radiopaque contrast technique. Reciproc showed enhanced apical volume changes and K3XF exhibited better centring ability when compared with other groups.